The Influence of Transformational Leadership Style and Work Discipline on Job Performance among Maros District Education Office Employees - Rosdiana Rosdiana; Andi Syahrum; Rina (Fakultas Ekonomi & Bisnis Universitas Muslim Indonesia, 2023)
This study aims to analyze the effect of transformational leadership style and work discipline on the work performance of employees of the Maros District Education Office. This study uses a descriptive approach (descriptive research) and an explanatory approach (explanatory research). The population in this study was 120 employees, and the sample was 92 people. The sample technique used was stratified proportional random sampling. The analysis technique used was multiple regression analysis through the SPSS 25 program. The results showed that leadership style variables, especially charisma, individual consideration, and intellectual stimulation, had a positive but not significant relationship to employee performance, and work discipline had a positive and significant relationship to employee achievement.